Ferroelectric Orthorhombic ZrO2 Thin Films Achieved Through Nanosecond Laser Annealing - Anna P. S. Crema; Marian C. Istrate; Alexandre Silva; Veniero Lenzi; Leonardo Domingues; Megan O. Hill; Valentin S. Teodorescu; Corneliu Ghica; Maria J. M. Gomes; Mario Pereira; Luís Marques; Judith L. MacManus‐Driscoll; et al. (Advanced Science, 2023)
Abstract A new approach for the stabilization of the ferroelectric orthorhombic ZrO2 films is demonstrated through nanosecond laser annealing (NLA) of as‐deposited Si/SiOx/W(14 nm)/ZrO2(8 nm)/W(22 nm), grown by ion beam sputtering at low temperatures. The NLA process optimization is guided by COMSOL multiphysics simulations. The films annealed under the optimized conditions reveal the presence of the orthorhombic phase, as confirmed by X‐ray diffraction, electron backscatter diffraction, and transmission electron microscopy. Macroscopic polarization‐electric field hysteresis loops show ferroelectric behavior, with saturation polarization of 12.8 µC cm−2, remnant polarization of 12.7 µC cm−2 and coercive field of 1.2 MV cm−1. The films exhibit a wake‐up effect that is attributed to the migration of point defects, such as oxygen vacancies, and/or a transition from nonferroelectric (monoclinic and tetragonal phase) to the ferroelectric orthorhombic phase. The capacitors demonstrate a stable polarization with an endurance of 6.0 × 105 cycles, demonstrating the potential of the NLA process for the fabrication of ferroelectric memory devices with high polarization, low coercive field, and high cycling stability.